Science Gamification on Engagement and Academic Performance: A Compendium of Interactive Tools Basis for Enhancement Program - Jarina, Meryl (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the effect of interactive games on students’ engagement and academic achievement in science. Anchored on the Theory of Gamified Learning and supported by Constructivist Learning Theory, the study examined how game-based activities influence behavioral, emotional, and cognitive engagement, as well as science performance. A quantitative quasi-experimental research design using pre-test and post-test procedures was employed. The study involved 39 Grade 11 students from Guindaruhan National High School in Minglanilla, Cebu, with 20 students assigned to the experimental group and 19 students assigned to the control group. The experimental group learned science through interactive games, while the control group received traditional lecture-based instruction. Data were gathered using an adapted student engagement questionnaire, classroom observations, academic evaluations, and a 25-item science test. Means, weighted averages, paired t-tests, and independent samples t-tests were used to analyze the data. Findings revealed that both groups improved in engagement and science achievement after instruction; however, the experimental group obtained higher gains in engagement and examination performance. The experimental group’s engagement increased from high to very high, while its science performance improved from low mastery to high mastery. Significant differences between the groups confirmed that interactive games were more effective than traditional instruction in improving engagement and academic achievement. The study supports SDG 4 on Quality Education, SDG 9 on Industry, Innovation and Infrastructure, and SDG 10 on Reduced Inequalities by highlighting innovative, technology-supported, and accessible teaching strategies. Its sustainability impact lies in promoting learner-centered science instruction, improving resource use, and supporting institutional efforts toward more engaging and inclusive education.
Keywords: Academic Achievement; Gamified Learning; Interactive Games; Science Education; Student Engagement; Technology-Based Instruction